Complex motor-cognitive factors processed in the anterior nucleus of the thalamus: an intracerebral recording study - Bočková, Martina; Chládek, Jan; Jurák, Pavel; Halámek, Josef; Štillová, Klára; Baláž, Marek; Chrastina, Jan; Rektor, Ivan (Brain topography, 2015)
Cognitive adverse effects were reported after the deep brain stimulation (DBS) of the anterior nucleus of the thalamus (AN) in epilepsy. As the AN may have an influence on widespread neocortical networks, we hypothesized that the AN, in addition to its participation in memory processing, may also participate in cognitive activities linked with the frontal neocortical structures. The aim of this study was to investigate whether the AN might participate in complex motor-cognitive activities. Three pharmacoresistant epilepsy patients implanted with AN-DBS electrodes performed two tasks involving the writing of single letters: (1) copying letters from a monitor; and (2) writing of any letter other than that appearing on the monitor. The cognitive load of the second task was increased. The task-related oscillatory changes and evoked potentials were assessed. Local event-related alpha and beta desynchronization were more expressed during the second task while the lower gamma synchronization decreased. The local field event-related potentials were elicited by the two tasks without any specific differences. The AN participates in cognitive networks processing complex motor-cognitive tasks. Attention should be paid to executive functions in subjects undergoing AN-DBS.
Keywords: kognice; motorické dovednosti; hluboká mozková stimulace; Motor Skills; Reaction Time; gama rytmus EEG; magnetická rezonanční tomografie; Anterior Thalamic Nuclei; evokované potenciály; Alpha Rhythm; lidé středního věku; nuclei anteriores thalami; Drug Resistance; psaní; alfa rytmus EEG; Magnetic Resonance Imaging; lidé; reakční čas; Adult; Middle Aged; dospělí; Beta Rhythm; Evoked Potentials; léková rezistence; beta rytmus EEG; Female; Writing; Epilepsy; Male; ženské pohlaví; Cognition; Humans; mužské pohlaví; Gamma Rhythm; Visual Perception; Electroencephalography; epilepsie; elektroencefalografie; Deep Brain Stimulation; zraková percepce